THE PHILOSOPHICAL BASIS OF GREBEG PANCASILA IN THEMATIC LEARNING OF ELEMENTARY STUDENTS - Septinaningrum (Universitas Majalengka, 2023)
Grebeg Pancasila is a local culture of Blitar, East Jawa, which is rich in symbols and meanings. However, the study of the meaning of Grebeg Pancasila is not understood in depth and is only limited in knowing, not yet reaching the feeling and acting stage. This study aims to analyze 1) the essence of Grebeg Pancasila; 2) The form of Grebeg Pancasila; 3) Stages of Grebeg Pancasila; 4) the meaning of thematic learning; and 5) learning implementation in Elementary Schools. Descriptive research using qualitative approach was used to conduct this study. Some participants such as the head of education and culture office, society, and elementary teachers and students were involved in this study. Several open questions were listed to interview the participants. Meanwhile, field notes were written when observing the Grebeg Pancasila rites and thematic learning activities in elementary schools. The data got from the interview and observation was analyzed qualitatively by using thematic analysis.. The results of the study show that Grebeg Pancasila is a tradition of people in Blitar Town, East Jawa which is intended to commemorate the birthday of Pancasila as the noble cultural value in Indonesian nation. In Grebeg Pancasila, there are several series of activities which include the Bedhol Pusaka Nagari, Malam Tirakatan, Cultural Ceremonies, and Kirab Gunungan Lima, and ended by Kenduri Pancasila. The series of activities and values contained in Grebeg Pancasila can be used as a basis for developing a value learning model, especially in the context of thematic learning at the elementary school level. Grebeg Pancasila merupakan salah satu budaya lokal Blitar Jawa Timur yang kaya simbol dan makna. Akan tetapi, kajian mengenai makna setiap ritus Grebeg Pancasila kurang dipahami secara mendalam dan hanya sebatas knowing belum sampai pada tahap feeling dan acting. Studi ini bertujuan menganalisis tentang (1) Hakikat ritus Grebeg Pancasila; (2) Bentuk ritus Grebeg Pancasila; (3) Tahapan ritus Grebeg Pancasila; (4) makna pembelajaran tematik; serta (5) Implementasi Pembelajaran di Sekolah Dasar. Penelitian deskriptif dengan pendekatan kualitatif digunakan untuk melakukan studi ini. Beberapa partisipan seperti: Kepala Dinas Pendidikan dan Budaya, masyarakat, dan guru dan siswa SD dilibatkan dalam studi ini. Beberapa pertanyaan terbuka didaftar untuk melakukan wawancara dengan partisipan. Sementara itu, beberapa catatan lapangan dibuat ketika melakukan observasi terhadap ritus Grebeg Pancasila dan aktivitas pembelajaran tematik di SD Kota Blitar. Data yang diperoleh dari wawancara dan observasi dianalisis secara kualitatif dengan tematik analisis. . Hasil penelitian menunjukan bahwa Gerebeg Pancasila merupakan tradisi masyarakat Blitar Jawa Timur yang ditujukan untuk memperingati hari lahirnya Pancasila sebagai nilai luhur budaya bangsa Indonesia. Pada kegiatan Grebeg Pancasila terdapat beberapa rangkaian kegiatan yang meliputi bedhol pusaka nagari, malam tirakatan, upacara budaya, kirab gunungan lima, dan diakhiri dengan kenduri pancasila. Rangkaian kegiatan dan nilai yang terdapat pada ritus Grebeg Pancasila dapat dijadikan landasan pengembangan model pembelajaran nilai, terutama dalam konteks pembelajaran tematik di jenjang sekolah dasar.